Extremity injuries sustained by the UK military in the Iraq and Afghanistan conflicts: 2003–2014. Issue 7 (July 2017) - ,; Penn-Barwell, J.G.; Bennett, P.M.; Fries, C.A.; Kendrew, J.M.; Midwinter, M.; Bishop, J.; Rickard, R.F.; Sargeant, I.D.; Porter, K.; Rowland, T.; Mountain, A.; et al.
Abstract: Introduction: Extremity injuries predominate in warfare, however their nature, and overall burden to the individual and the health service is yet to be characterised for the UK military in the recent conflicts of Iraq and Afghanistan. Methods: We reviewed the all extremity injuries in survivors from the Joint Theatre Trauma Registry (JTTR) between 2003 and 2014. All cases recorded in the JTTR between the invasion of Iraq on the 19th March 2003 and cessation of combat operations in Afghanistan on the 27th October 2014, were examined. Casualties who were killed in action or died from their wounds were excluded. All extremity injury codes were included, capturing patients with soft tissue injuries but no fracture or amputation. Results: Of 2348 UK combatants surviving injury in Iraq and Afghanistan, 1813 (77%) had extremity injuries; of these 205 (11%) had at least one amputation at the wrist/ankle or more proximal. Trans-tibial was the most common level of limb loss. Eighty five casualties lost 2 limbs, 83 of these (98%) lost both lower limbs and 17 lost 3 limbs. Aside from amputations, there were 1530 fractures, 501 (33%) involving the upper limb and 1029 (67%) in the lower limb and pelvis. The tibia was the most frequently fractured bone. Of the lower limb fractures, 597 (58%) were open compared with 344 (69%) in the upper limb. Total Length of Stay (LOS) following extremity injury was 24, 486 days or 69 years and 1 month; there were a total 2817 surgical episodes performed on extremities. Median length of stay Length of Stay (LOS) for major amputations (i.e. those at the wrist/ankle or more proximal) was 51 days (IQR 30–65) with a median of 7 surgical procedures on their limbs (IQR 5–9). In casualties with fractures but no amputation, median LOS was 13 days (IQR 6–25) with a median of 2 surgical procedures (IQR 1–4). Conclusion: Utilising a dedicated injury database, this study illustrates for the first time in the United Kingdom military population, that the extremities are involved in the vast majority of combat injuries and the large surgical workload required for their treatment.